Diversification across the New World within the 'blue' cardinalids (Aves: Cardinalidae). (14th October 2013) - Bryson, Robert W.; Chaves, Jaime; Smith, Brian Tilston; Miller, Matthew J.; Winker, Kevin; Pérez‐Emán, Jorge L.; Klicka, John; Bush, Mark
Abstract Aim To examine the history of diversification of 'blue' cardinalids (Cardinalidae) across North and South America. Location North America (including Middle America) and South America. Methods We collected 163 individuals of the 14 species of blue cardinalids and generated multilocus sequence data (3193 base pairs from one mitochondrial and three nuclear genes) to infer phylogeographical structure and reconstruct time‐calibrated species trees. We then estimated the ancestral range at each divergence event and tested for temporal shifts in diversification rate. Results Twenty‐five lineages of blue cardinalids clustered into two major clades: one confined to North America, and a second concentrated in South America. Blue cardinalids probably originated in North America, but reconstructions were influenced by how migrant taxa were assigned to biogeographical regions. Most of the pre‐Pleistocene divergences between extant taxa occurred in the North American clade, whereas most divergences in South America and adjacent Middle America occurred during the Pleistocene. Despite these differences, the rate of diversification for both clades has been similar and relatively constant over the past 10 million years, with little geographical exchange between North and South America outside the Panamanian isthmus region. Main conclusions Our reconstruction of the diversification history of blue cardinalids indicates a role of both Neogene and Quaternary events in generating biotic diversity across North and South America. Although ancestral area reconstruction suggests a possible North American origin for blue cardinalids, the occurrence of seasonal migration in this group and their relatives limits inference. Our study highlights the importance of considering ecological and behavioural characteristics together with palaeogeological events in order to gain an understanding of the diversification history of widespread, mobile taxonomic groups.